Lipofibromatous hamartoma of the digital branches of the median nerve presenting as carpal tunnel syndrome: A rare case report with review of the literature - Ranjan Agrawal (Indian Journal of Pathology and Microbiology, 2016)
Lipofibromatous hamartoma (LFH) is a rare, benign fibrofatty tumor composed of a proliferation of mature adipocytes within peripheral nerves, which form a palpable neurogenic mass. It affects the median nerve in 66-80% of cases, causing pain and sensory and motor deficits in the affected nerve distribution. Patients typically present with gradually enlarging nontender lesions in the distribution of the affected nerve. The lesion is also seen to be associated with macrodactyly. The pathophysiology of LFH is unknown. Treatment of LFH is based on symptoms of the condition. Histopathology is characteristic. We present a case of young male diagnosed as lipofibromatous hamartoma of the median nerve involving the right index finger. The case is presented due to its rarity.